First molecular characterisation and PCR ribotyping of Clostridium difficile strains isolated in two Algerian Hospitals - Djebbar, Abla; Sebaihia, Mohammed; Kuijper, Ed; harmanus, Celine; Sanders, Ingrid; Benbraham, Nadia; Hacène, Hocine (The Journal of Infection in Developing Countries, 2018)
Introduction: Clostridium difficile is the major etiological agent of nosocomial antibiotics associated diarrhoea. C. difficile infection is associated with considerable morbidity and mortality among hospitalized patients worldwide. Despite its known importance, there is no study on this important pathogen in Algeria. Methodology: In this prospective study, undertaken between 2013 and 2015, faecal specimens were collected from 159 hospitalized patients with antibiotic-associated diarrhoea in two tertiary health care hospitals in Chlef, Algeria. Faecal samples were cultured on CLO plates Agar with cefoxitin, cycloserine antibiotics and sodium taurocholate. C. difficile suspected colonies were analysed by multiplex PCR for the detection of the toxin genes. C. difficile isolates were analysed by PCR ribotyping and multi-locus tandem repeat analysis. Antimicrobial susceptibility was determined by the E-test method, according to the Clinical and Laboratory Standards Institute protocol. Results: C. difficile was cultured from 11 of 159 stool specimen (6.9%). Seven strains were toxigenic, mainly represented by the 020 and 014 PCR ribotypes and four non toxigenic belong to PCR ribotype 084. All 11 isolates were susceptible to both vancomycin and metronidazole and resistant to ciprofloxacin. Conclusions: This study, which reported for the first time C. difficile ribotypes circulating in Algerian health care facilities, could paves the way for further more comprehensive studies on this important pathogen, and could be useful to the local health authorities to implement a surveillance program of C. difficile in Algeria.